Cadmium and Lead Contamination in Highland Honey from Peru: A Potential Health Risk. - Llico-Saénz, C.E. (2025)
Introduction. Honey has been part of the human diet and medicine for millennia. Although its nutritional composition can vary across regions, the concentration of certain metals must not exceed the maximum permissible limits (MPLs) set by national and international bodies, as these metals are toxic to consumers. Objectives. To determine the concentration of cadmium and lead in honey from two districts (Cajamarca and La Encañada) in a northern province of Peru. Materials and Methods. Twelve samples werecollected from four localities in these two districts of the Cajamarca province. Cd and Pb concentrations were measured using graphite furnace atomic absorption spectrophotometry. Results and Discussion. Cd levels ranged from 0.070 to 2.875 mg/kg, while Pb levels varied from <0.001 to 2.478 mg/kg. The highest Cd concentrations were found in honey from the Cajamarca district and its two localities; however, these differences were not statistically significant (p>0.05). Honey from La Encañada and its localities showed the highest Pb levels (p<0.05). Compared to MPLs established by Mercosur (Cd: 0.10 mg/kg; Pb: 0.30 mg/kg), 91.67% (95% CI: 61.52 - 99.79) of the samples exceeded these limits for Cd, with increases of up to 2775%. Similarly, 58.33% (95% CI: 27.67 - 84.83) of the samples exceeded MPLs for Pb, with increases of up to 726%. Conclusions. Honey samples from two northern Peruvian districts exhibited Cd and Pb levels above Mercosur MPLs, posing potential health risks for consumers and rendering the honey unsuitablefor trade.